The Power of Global Community Media
XIX, 272 p.
Keywords: Drawing on both theoretical and practical case studies, this collection moves from developing attempts at local media to case studies and on to cyber-examples. The contributors, all distinguished international communications scholars, present a range of perspectives on the ever-burgeoning area of grassroots, local media.